1986
DOI: 10.1039/c39860001272
|View full text |Cite
|
Sign up to set email alerts
|

Copper(II) ion-exchanged ZSM-5 zeolites as highly active catalysts for direct and continuous decomposition of nitrogen monoxide

Abstract: ZSM-5 zeolites containing Cu2+ ions showed unusually high and steady state activity for the catalytic decomposition of nitrogen monoxide; for example, the degrees of conversions of NO, and of conversion into N2 and O2 were 97, 85, and 70°/0, respectively, at 823 K with a contact time of 10.0 g s cm-3 over 73% exchanged Cu-ZSM-5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
315
1
3

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 517 publications
(327 citation statements)
references
References 1 publication
5
315
1
3
Order By: Relevance
“…A whole series of catalysts was explored over the last 50 years, but no appreciable reaction rates were obtained till the epochmaking finding of Iwamoto et al in 1986 [5]. They reported the uniquely high and stable activity of overexchanged Cu-ZSM-5 for the direct NO decomposition [5]. However, tests under conditions representative of automotive exhaust gases pointed toward two important limitations of Cu-ZSM-5 for a practical application: (1) a too low activity by 1-2 orders of magnitude and (2) the suppression of the activity by water vapor and SO 2 [1].…”
Section: Introductionmentioning
confidence: 99%
“…A whole series of catalysts was explored over the last 50 years, but no appreciable reaction rates were obtained till the epochmaking finding of Iwamoto et al in 1986 [5]. They reported the uniquely high and stable activity of overexchanged Cu-ZSM-5 for the direct NO decomposition [5]. However, tests under conditions representative of automotive exhaust gases pointed toward two important limitations of Cu-ZSM-5 for a practical application: (1) a too low activity by 1-2 orders of magnitude and (2) the suppression of the activity by water vapor and SO 2 [1].…”
Section: Introductionmentioning
confidence: 99%
“…Solid-state 31 P NMR spectra were recorded at 161.9 MHz with a spinning rate of 10 kHz, a π/2 pulse of 5 μs with 20 s repetition time. 29 Si, 27 Al and 31 P chemical shifts were referred to tetramethylsilane, Al 3+ (H 2 O) 6 , and 85% H 3 PO 4 , respectively.…”
Section: The Chemical Analyses Were Carried Out In a Varian 715-es Icmentioning
confidence: 99%
“…The discovery of copper-exchanged zeolites as active and stable catalysts for the SCR of NOx by Iwamoto et al introduced an attractive alternative to vanadia-based materials [6]. Several metal-exchanged molecular sieves, primary medium and large pore zeolites, have been reported in the last two decades for the SCR of NOx [7].…”
Section: -Introductionmentioning
confidence: 99%
“…A variety of materials have been studied for their ability to catalyse these processes, and these include various kinds of zeolites, metal oxides and supported noble metal catalysts. Cu-ZSM-5, a copper ion-exchanged zeolite, has been reported to be a much more efficient catalyst for the elimination of NO than the earlier known catalysts for the catalytic reduction of this gas [24]. However, its activity decreases sharply with a decrease in the NO concentration, and it suffers from severe deactivation in the presence of oxygen or sulphur oxides [24].…”
Section: Catalytic Conversion Of Pollutants In Automobile Emissions Umentioning
confidence: 99%
“…Cu-ZSM-5, a copper ion-exchanged zeolite, has been reported to be a much more efficient catalyst for the elimination of NO than the earlier known catalysts for the catalytic reduction of this gas [24]. However, its activity decreases sharply with a decrease in the NO concentration, and it suffers from severe deactivation in the presence of oxygen or sulphur oxides [24]. In another study, it was found that Ga-ZSM-5 and In-ZSM-5 catalysts were highly active and selective for NO reduction by CH 4 .…”
Section: Catalytic Conversion Of Pollutants In Automobile Emissions Umentioning
confidence: 99%